2021
DOI: 10.3389/fphar.2021.756924
|View full text |Cite
|
Sign up to set email alerts
|

Phillygenin Attenuates Carbon Tetrachloride-Induced Liver Fibrosis via Modulating Inflammation and Gut Microbiota

Abstract: Liver fibrosis is a chronic pathological process that various pathogenic factors lead to abnormal hyperplasia of hepatic connective tissue, and its main feature is the excessive deposition of extracellular matrix. However, there are currently no drugs approved for the treatment of liver fibrosis. Phillygenin (PHI), a lignan isolated from Forsythiae Fructus, showed potential anti-inflammatory and anti-fibrosis effects but the mechanisms remain unknown. In view of the vital role of gut microbiota in the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
(51 reference statements)
2
18
0
Order By: Relevance
“…let-7b significantly ameliorated the mice colitis and reduced the secretion of inflammatory cytokines through TLR4. Another study showed that phillygenin could improve inflammation and fibrosis caused by CCl 4 [ 4 ]. Furthermore, it restored the intestinal barrier by promoting ZO-1, occludin, and claudin-1.…”
Section: Experimental Results Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…let-7b significantly ameliorated the mice colitis and reduced the secretion of inflammatory cytokines through TLR4. Another study showed that phillygenin could improve inflammation and fibrosis caused by CCl 4 [ 4 ]. Furthermore, it restored the intestinal barrier by promoting ZO-1, occludin, and claudin-1.…”
Section: Experimental Results Analysismentioning
confidence: 99%
“…Furthermore, it restored the intestinal barrier by promoting ZO-1, occludin, and claudin-1. Phillygenin enriches the relative abundance of Lactobacillus and regulated the intestinal microbiota, which are reported to effectively alleviate the intestinal barrier injury [ 4 ]. Recent study also found that phillygenin also inhibited LPS-induced inflammation through TLR4/MyD88 signaling and suppress the adaptive immune response and inflammatory activities.…”
Section: Experimental Results Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, phillygenin, which is an effective antibacterial component of F. suspensa belonging to the lignans, was screened out (Liu et al, 2018 ). Studies have reported that phillygenin had the effects of regulating the intestinal microbiota, reducing fibrosis herein (Sun et al, 2021 ), inhibiting the release of inflammatory cytokines (Wang et al, 2021 ), inhibiting adhesion and migration, etc. (Quan et al, 2021 ), while, less has been studied about its antibacterial effects.…”
Section: Discussionmentioning
confidence: 99%